Incorporating stakeholder perspectives in developing a translation table framework for comparative effectiveness research. (May 2012) - Gliklich, Richard E; Leavy, Michelle B; Velentgas, Priscilla; Dreyer, Nancy A; Tunis, Sean R; Mohr, Penny; Messner, Donna A; Moloney, Rachael M; Karkare, Swapna U; Dubois, Robert W; Graff, Jennifer S
This project used a stakeholder-driven process to understand the factors that drive the selection of study designs for comparative effectiveness research (CER). The project assembled a diverse stakeholder committee to explore the basis of a translation framework and gathered input through surveys, interviews and an in-person meeting. Stakeholders recommended different study designs for the CER topic areas and identified different outcomes as the most important outcomes to study in each area. During the discussions, stakeholders described a variety of factors that influenced their study design recommendations. The stakeholder activities resulted in the identification of several key themes, including the need to have a highly specific detailed research question before discussing appropriate designs and the need to use multiple studies, potentially of different designs, to address the CER topic areas. The insights and themes from this project may inform efforts to develop a translation table.